The Effect of The Self-efficiency of Individuals on The Fear of Missing During The Covid-19 Pandemic Process - Korkmaz, Sezer; Taş, Merve Özzeybek; Özşahin, Figen (Fırat University, 2022)
Purpose: The aim of this study is to examine the effect of individuals' self-efficacy on the fear of missing out during the covid-19 pandemic process. Method: The sample of this study, which has a relational nature, consists of 660 people over the age of 18 from across the country. The study was carried out with questionnaire forms shared via the internet. In order to determine the personal characteristics of individuals in the questionnaire, the Personal Information form develop In order to determine the personal characteristics of the individuals in the questionnaire “The Personal Information form” developed by the researchers was used with “Self-Efficacy Scale” developed by Sherer et al. (1982), adapted into Turkish by Yıldırım and İlhan (2010) and “The Fear of Missing Out Scale” developed by Przyblski et al. (2013), adapted into Turkish by Gökler et al. (2016). Findings: In the study, self-efficacy does not differ according to gender and education level. Fear of missing out, on the other hand, does not differ according to gender, but differs according to educational status. In addition, it can be stated that the increase in the self-efficacy of individuals will have an effect on reducing their fear of missing out on developments. Discussion: As a result of the research, it was found that self-efficacy affects the fear of missing out. In this study, it was stated that the most trusted source from the sources about Covid-19 was the Ministry of Health.

Amaç: Bu çalışmanın amacı covid-19 pandemisi sürecinde bireylerin özyeterliliğinin, gelişmeleri kaçırma korkusu üzerindeki etkisinin incelenmesidir. Yöntem: İlişkisel bir niteliği olan bu çalışmanın örneklemini, ülke genelindeki 18 yaş üstü olan 660 kişi oluşturmaktadır. Çalışma internet aracılığı ile paylaşılan anket formları ile gerçekleştirilmiştir. Anket içerisinde bireylerin kişisel özelliklerini belirlemek amacıyla araştırmacıların geliştirmiş olduğu Kişisel bilgi formu ile Sherer vd. (1982) tarafından geliştirilen ve Yıldırım ve İlhan (2010) tarafından Türkçe’ye uyarlanan “Özyeterlilik Ölçeği” ile Przyblski vd. (2013) tarafından geliştirilen ve Gökler ve arkadaşları (2016) tarafından Türkçeye uyarlanan “Gelişmeleri Kaçırma Korkusu Ölçeği“ kullanılmıştır. Bulgular: Araştırmada özyeterlilik cinsiyete göre farklılaşmamaktadır. Ayrıca özyeterlilik eğitim düzeyine göre de farklılaşmamaktadır. Gelişmeleri kaçırma korkusu ise cinsiyete göre farklılaşmazken eğitim durumuna göre farklılaşmaktadır. Ayrıca bireylerin özyeterliliğinin artmasının gelişmeleri kaçırma korkusu yaşamalarını azaltacak yönde etki edeceği ifade edilebilmektedir. Tartışma: Araştırma sonucunda, özyeterliliğin gelişmeleri kaçırma korkusunu etkilediği bulunmuştur. Bu çalışmada Covid-19 ile ilgili bilgi edinilen kaynaklardan en çok güvenilen kaynağın Sağlık Bakanlığı olduğu belirtilmiştir.
COVİD-19 PANDEMİSİ SÜRECİNDE BİREYLERİN ÖZYETERLİLİĞİNİN GELİŞMELERİ KAÇIRMA KORKUSU ÜZERİNDEKİ ETKİSİ